2023
DOI: 10.3389/fpls.2023.1104095
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi affect the expression of PxNHX gene family, improve photosynthesis and promote Populus simonii×P. nigra growth under saline-alkali stress

Abstract: IntroductionSaline-alkali stress seriously endangers the normal growth of Populus simonii×P. nigra. Arbuscular mycorrhizal (AM) fungi can enhance the saline-alkali tolerance of plants by establishing a symbiotic relationship with them.MethodsIn this study, a pot experiment was conducted to simulate a saline-alkali environment where Populus simonii×P. nigra were inoculated with Funneliformis mosseae to explore their effects on the saline-alkali tolerance of Populus simonii×P. nigra.Results and DiscussionOur res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…AMF colonization alleviates this stress by promoting plant root elongation, which expands the water absorption area of plants to relieve water shortage in plant cells, thus inhibiting stomatal closure, reducing chloroplast damage, and improving the efficiency of light energy utilization. This is consistent with previous studies on black locust, Xanthoceras sorbifolium, and Populus simonii [6,39,69].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…AMF colonization alleviates this stress by promoting plant root elongation, which expands the water absorption area of plants to relieve water shortage in plant cells, thus inhibiting stomatal closure, reducing chloroplast damage, and improving the efficiency of light energy utilization. This is consistent with previous studies on black locust, Xanthoceras sorbifolium, and Populus simonii [6,39,69].…”
Section: Discussionsupporting
confidence: 93%
“…In rice, Turan et al [ 67 ] found that salt stress inhibits chlorophyll biosynthesis intermediates to reduce the accumulation of chlorophyll. In addition, AMF colonization relieves the damage to photosynthesis performance under stress by regulating photosynthetic activity (Pn, Ci, and Tr), water content, and stomatal conductance (Gs) [ 6 , 68 ]. In this study, the Gs, Pn, Ci, and Tr levels of the AMF group were dramatically higher than those of the non-AMF group under salt stress, similar to water content, water saturation deficit, and chlorophyll content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is worth mentioning that the interaction of P. microphylla with arbuscular mycorrhizal fungi is also crucial for improving salt-alkali tolerance. Fengxin Dong's research shows [37] that related interactions can change the expression pattern of PxNHXs, thereby affecting photosynthesis and ion absorption to enhance related salt-alkali to-lerance. If the nitrogen absorption efficiency of P. simonii is improved under saline-alkali stress, the damage caused by the stress can also be reduced [38].…”
Section: Research Progress Of P Simonii Genomicsmentioning
confidence: 99%
“…Na + is transported via the apoplastic and symplastic ways from the root xylem to leaves, where it is necessary to maintain an efficient Na + control and intracellular compartmentalization in the vacuoles (Bojórquez‐Quintal et al, 2014) to minimize the cytotoxicity. If salinity ions are sequestered in the leaf's vacuoles, compatible osmolytes must accumulate in the cytosol to balance the osmotic pressure in the vacuole (Assaha et al, 2017; Dong et al, 2023). The compatible solutes that plants accumulate most commonly are sucrose, proline, glycine betaine and polyols (Hasegawa et al, 2000; Munns, 2005; Choudhary et al, 2023), which contents are controlled by many genes (Hare et al, 1998; Acosta‐Motos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%